The Influence Of Nutrition Knowledge And Pocket Money On Instant Noodle Consumption In Students - Fatonah, Siti; Yuliana, Yuliana; Fridayanti, Lucy; Kasmita, Kasmita (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research is motivated by several problems, namely students still often consume instant noodles with high frequency, students have knowledge but do not apply it in their food consumption, some students have low income so they cannot afford quality food. The purpose of this study was to analyze the effect of nutritional knowledge and pocket money on student instant noodle consumption. The type of research used is quantitative with a causal associative approach. The population of this research is active students of the Faculty of Tourism and Hospitality. The research sample was 189 people with the sampling technique using proportional random sampling. The type of data used in this research is primary data. The data collection technique used a questionnaire with a Likert scale and Guttman scale which had been tested for validity and reliability. The data were processed descriptively using multiple linear regression using SPSS version 26.00.The results showed that the average nutritional knowledge of students was in the sufficient category (32.28%). The average student pocket money is in the moderate category (44.44%). Consumption of instant noodles is in the medium category (37.57%). Knowledge of nutrition and pocket money can explain consumption of instant noodles with an adjusted R Square of 0.112, where there is an effect of knowledge of nutrition and pocket money on instant noodle consumption of 11.2%. Then the Fcount value is 12.853 with a sig value of 0.000 <0.05 so it can be concluded that nutrition knowledge and pocket money together have a significant effect on student instant noodle consumption.